Histopathology And Hematology Of Epizootic Ulcerative Syndrome (Eus)-Positive Snakehead (Ophicephalus Striatus) - Lacierda, Erlinda C (1995)

(untitled)
Epizootic ulcerative syndrome is an ulcerative disease of wild and cultured freshwater fishes in Asia and the Pacific . Despite the bulk of research done on the syndrome for the past 10 years , the primary pathogen remains an enigma . This study was undertaken to understand the progressive development of EUS lesions through histopathology and hematology of EUS - positive snake head ( Ophicephalus striatus ) . Regular monitoring of snakeheads in Laguna de Bay , Philippines from October 1990 to February 1993